(3GdbhGYO GdcHQis - (3YHO GdYRjR Hf YHO GdSdGe Hf CHj GdbGSe Hf GdMSf GdSdej GdOeTbj, YR GdOjf GdedbH HSdWGf GdYdeGA,J (B660 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO efg jdYf GdQLd hGdOjg bGd jSH CHG GdQLd ajSH CHGg hCeg LYd GddYf ef CcHQ GdcHGFQ s
(3BNQgG (B:s
(3Gddge aGQTOfG Edi GdMb hCgOfG Edi GdUhGH hgh MSHfG hfYe Gdhcjd BNQ cJGH s
(3Ydi MhGTjgG JUMjMGJs
(3jXf HYV bQGA GdfSNI CfgG HNW GdeDdas
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B21 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B249s
Keywords: (3CUhd Gdabgs